Prevention of Osteoporosis in the Ovariectomized Rat by Oral Administration of a Nutraceutical Combination That Stimulates Nitric Oxide Production. (2nd June 2019) - Rajfer, Rebecca A.; Flores, Manuel; Abraham, Andrea; Garcia, Eduardo; Hinojosa, Natalhy; Desai, Mina; Artaza, Jorge N.; Ferrini, Monica G.
Abstract : Osteoporosis represents an imbalance between bone formation and bone resorption. As a result of low estrogen levels, it is markedly prevalent during menopause, thus making such patients susceptible to fractures. Both bone formation and resorption are modulated by nitric oxide (NO). Currently, there are no risk-free pharmaceutical prevention therapies for osteoporosis. COMB-4, a nutraceutical combination of Paullinia cupana, Muira puama, ginger, and L-citrulline, known to activate the NO-cGMP pathway, was reported to accelerate fracture healing in the rat. To determine whether COMB-4 could be effective in preventing menopausal osteoporosis, it was compared to estradiol (E2) in an ovariectomized (OVX) rat osteoporosis model. Nine-month-old female Sprague Dawley rats were divided into SHAM, OVX, OVX+E2, and OVX+COMB-4. After 100 days of treatment, bone mineral density (BMD) and bone mineral content (BMC) were measured by DXA scan. TRAP staining was performed in the femur and lumbar vertebrae. TRACP 5b and osteocalcin levels were assayed in the serum. MC3T3-E1 cells were differentiated into osteoblasts and treated with COMB-4 for one week in order to evaluate calcium deposition by Alizarin staining, cGMP production by ELISA, and upregulation of the nitric oxide synthase (NOS) enzymes by RT-PCR. OVX resulted in a decrease in BMD, BMC, and serum osteocalcin and an increase in serum TRACP 5b. Except for an increase in BMC with COMB-4, both E2 and COMB-4 reverted all bone and serum markers, as well as the number of osteoclasts in the vertebrae, to SHAM levels. Incubation of MC3T3-E1 cells with COMB-4 demonstrated an increase in the three NOS isoforms, cGMP, and calcium deposition. COMB-4 increased BMD in OVX rats by inhibiting bone resorption and increasing calcium deposition presumably via activation of the NO-cGMP pathway. It remains to be determined whether COMB-4 could be a potential nutraceutical therapy for the prevention of premenopausal bone loss.